Enhancing tumor vaccines: catalyzing MHC class II peptide exchange. (February 2010) - Croft, Nathan P; Purcell, Anthony W
Evaluation of: Dickhaut K, Hoepner S, Eckhard J et al. Enhancement of tumour-specific immune responses in vivo by ''MHC loading-enhancer'' (MLE). PLoS One 4(9), e6811 (2009). Peptide vaccination strategies aimed at inducing CD4 + T-cell responses may be hampered due to the poorly receptive nature of MHC class II molecules to exogenous antigen. It has recently been reported that the small organic molecule adamantane ethanol, when included as an adjuvant in peptide vaccination, is capable of enhancing ligand exchange and markedly augmenting the subsequent antigen-specific CD4 + T-cell response. These results highlight a novel adjuvant strategy tested in vivo, which opens a further doorway to improving the efficacy of peptide vaccination and continuing the push towards clinical trials.